Knowledge of Cholera Among Syrians: A Cross-Sectional Study - Almoshantaf, Mohammad Badr; Swed , Sarya; Alibrahim, Hidar; Bohsas, Haidara; Nasif, Mohmad Nour; Hafez, Wael; Aldaas, Ahmad (International Journal of Medical Students, 2023)
Background: Cholera is a communicable acute bacterial infection caused by a gram-negative bacterium that is Vibrio Cholera. Worldwide, is estimated that an incidence of 1.3–4.0 millions of cholera infection, leading to 21,000–143,000 deaths annually. Prevention of cholera require a proactive approach rather than reactive, as it`s identified to be the best strategy to decrease the cholera spreading risk in given population or community. Recently WHO warned that, the cholera spreading risk in Syria is very high, which linked to drinking of untreated water and food contamination. Aim: we conducted this study with aiming to assess the level of knowledge, attitude and practice regarding risks of cholera infection, preventive measures and preparedness among community in Syria. Consequently, recommending suitable measures based on study results. Methods: An online cross-sectional study was conducted in Syria to assess knowledge, attitude, and practice regarding cholera and cholera vaccine among general population in Syria. The inclusion criteria for participation were Syrian nationality aged 18 or more, male or female, from all governorates of Syria, never have cholera previously, and were willing to participate. The questionnaire was consisting of four sections. The first section was about sociodemographic data. The second section evaluated respondents' self-reported knowledge on cholera and divided into two parts (2a: Knowledge on cholera, its prevention and treatment. 2b Knowledge on cholera vaccine). The third section evaluated respondents’ self-reported practice relating to cholera and its vaccine, this section divided into two parts (3a: Practice relating cholera and its treatment/management. 3b: Practice relating cholera vaccine. The fourth section inquired respondents’ attitude toward cholera and cholera vaccine. 52.9% thought that cholera outbreaks happen in summer seasons. Results: Among 1563 Syrian national participants, (n=982, 62.8%) were females, and (n=581, 37.2%) males. 60.9% of respondents did not recognize the cholera in the first place. Passing watery stool was the most recognized symptom of cholera with 50.3%, severe dehydration with 31.1%, and repeated vomiting with 10.3%. Lack of safe drinking water was recognized as the most common cause for cholera. Most respondents (54.1%) have chosen IV saline as the treatment of choice for cholera. 85.3% of respondents are with providing health care to the infectants in health centers. Conclusion: According to our findings, there is insufficient understanding of the cholera symptoms and risk factors. The need for better understanding of such common outbreaks is essential to counter them. Consequently, there is a greater need to increase cholera awareness and education programs on the disease's signs and symptoms and its risk factors.